2019
DOI: 10.1371/journal.pone.0211857
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive disorders of pregnancy and peripartum cardiomyopathy: A nationwide cohort study

Abstract: Background Peripartum cardiomyopathy (PPCM) is a serious cardiac disorder occurring late in pregnancy or early in the postpartum period. We examined associations between hypertensive disorders of pregnancy (HDP: preeclampsia and gestational hypertension) and PPCM, accounting for other pregnancy-related risk factors for PPCM. Methods Using nationwide Danish register data, we constructed a cohort of all women with ≥1 live birth or stillbirth in Denmark between 1978 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 38 publications
2
29
0
6
Order By: Relevance
“…However, some other studies have reported prevalences similar to our study. 16,25,28 When we ran the sensitivity analysis including women with diagnoses for nonperipartum cardiomyopathy or other heart disease, the prevalence was 3.8 per 10,000 births-which is more in alignment with previous studies. Associations between obesity and peripartum cardiomyopathy remained but were somewhat attenuated when using this broader case definition.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, some other studies have reported prevalences similar to our study. 16,25,28 When we ran the sensitivity analysis including women with diagnoses for nonperipartum cardiomyopathy or other heart disease, the prevalence was 3.8 per 10,000 births-which is more in alignment with previous studies. Associations between obesity and peripartum cardiomyopathy remained but were somewhat attenuated when using this broader case definition.…”
Section: Discussionsupporting
confidence: 79%
“…2,8,16,[25][26][27] In particular, some have used diagnostic billing codes to identify obesity, which is known to have poor sensitivity 2,[25][26][27] or lacked access to postpartum records, although a large proportion of cases occur after childbirth hospitalization. 2,25 Some studies have also included women with other known heart conditions, which may misclassify women with peripartum cardiomyopathy, 25 had small sample sizes 16 or were restricted to maternal deaths related to peripartum cardiomyopathy although the vast majority of women survive. 8 The objective of this study was to determine the association of pre-pregnancy BMI with peripartum cardiomyopathy, using data from more than 2.5 million women who gave birth in California from 2007 to 2012.…”
mentioning
confidence: 99%
“…To explore the association between HDP and PPCM, a cohort study was done in Denmark by Behrens et al It identified 126 women with PPCM, 39 of whom developed HDP whereas 87 were normotensive [13]. Most cases (82% vs. 81.6%) were diagnosed either during the final month of pregnancy or the first month of postpartum, both in women with or without HDP.…”
Section: Reviewmentioning
confidence: 99%
“…Several studies have been carried out at different subpopulations in many countries that sheds light on the various common and different characteristics observed for the two phenomena. The reported incidence of HDP among PPCM patients ranges from 2-68%.In the most recent study by Behrens et al, a cohort of >2 million pregnant females across Denmark revealed that the risk of PPCM in women with HDP was 5-21 times higher than in normotensive women, and the risk increased with increasing severity of hypertension [13] (Figure 1).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation